Padrões espaciais de distribuição de espécies e de riqueza específica ao longo de um gradiente montante-jusante e na bacia do Rio dos Sinos (RS) - Brasil - Pereira, Joana Jordão (2018)
Distribution models are considered important tools in biogeography and ecology studies as they allow spatial and temporal extrapolation of species distribution from a set of occurrence data points as function of environmental predictors. In this study, we aimed to propose logistic distribution models for 50 fish species along the Sinos River Basin (Rio Grande do Sul, Brazil), by using altitude and basin area as geomorphological descriptors. Upstream-downstream richness model for entire basin by using multiple and logistic regression was also presented. The dataset derived from several sampling programs performed from 1998 to 2014, comprising 86 sampled locations with fish collections with gillnets, electric fishing or both. Two logistic models were constructed using environmental data of altitude and upstream basin area, testing linear (Model 1) and nonlinear (Model 2) factor responses for each species. Performance of the two models was evaluated using sensitivity, specificity, AUC (Area Under Curve) and TSS (True Skill Statistical). The adjusted models presented sensitivity values ranging from 47,1 to 99,8, specificity from 49,94 to 98,10, AUC from 0,75 to 0,99 and TSS from 0,26 to 0,98. The linear response model, although simpler, proved to be effective in predicting species distribution, as observed in previous studies. The basin area had a positive effect on the distribution of most species according to the linear model, although this was not verified for nonlinear models due to the interaction between variables. In general, the nonlinear model presented higher performance values for the evaluated metrics for the majority of species, but suffered from overfitting and a patchy distribution estimation. The species richness increased along a longitudinal gradient, presenting its maximum value downstream of the basin. Of the four estimated richness models, models with six variables were the ones with the lowest residual variation.